EBSD analysis of spark plasma sintered SS316-B4C composite. (March 2023) - Baranidharan, K.; Thirumalai Kumaran, S.; Uthayakumar, M.; Parameswaran, P.; Babu, D. Arvindha
Abstract: The Electron Backscatter Diffraction (EBSD) method has been characterized as a potential tool for analysing the microstructural changes that occur during the sintering processes and it possesses the ability to depict misorientation diagrams, pole figures and grain size distribution. The present work focuses on observing the microstructure evolution of the prepared 316 stainless steel with 10 wt% of B4 C samples sintered at the temperatures of 800, 900, and 1000 °C using the Spark Plasma Sintering (SPS) method. The samples are in the equiaxed form of recrystallized grains and they are elongated. Further, the samples sintered at 900 °C are equally recrystallized compared to other samples sintered at 800 and 1000 °C, where the microstructure is partially recrystallized with a high fraction. The result is explicable, by increasing the carbon content it causes the reduction of grain boundaries as well as decreases the migration rate of twin boundary generation. Hence, twin character loss is accelerated by the increase of carbon content with low-angle boundaries, and because of the typical drag effect, it has been discovered that the dynamically recrystallized grain size is reduced. The partitioning of these microstructures is done to differentiate the sintered sample and the recrystallized grains, based on the Grain Orientation Spread (GOS) map. The experimental investigation has suggested that the samples sintered at 900 °C has a more favourable microstructure analysis than the other samples sintered at 800 °C and 1000 °C, respectively. Highlights: EBSD pattern revealed deformed SS316 - 10 % B4 C composite at higher temperatures. Grain sizes and crystal morphology were identified using GAM, GOS, KAM and IPF. Composite deformed at 900 °C is better than other samples. Grain boundaries present in the sample are used to improve the resistance to failure.